Discover hidden taxa of Erysiphe section Erysiphe fungi (Ascomycota, Erysiphaceae) based on morphology and multilocus phylogeny in China - Zhao-Yang Zhang; Xue-Lian Wu; Xiao-Xue Lv; Tie-Zhi Liu; Dan-Ni Jin; Li Liu; Shuang-Bao Wang; Jing Feng; Tom Hsiang; Yu Li; Shu-Yan Liu (MycoKeys)
Erysiphe sect. Erysiphe, a taxonomically significant group within the genus Erysiphe, is distinguished from other Erysiphe sections by its mycelioid chasmothecial appendages. While approximately half of the known species in this section occur in China, our preliminary assessments suggest that a substantial number of cryptic taxa remain undetected. To address this knowledge gap, we conducted a comprehensive phylogeographic survey evaluating 78 specimens collected from 18 provinces (municipalities/autonomous regions) across China. Our integrative approach combined morphological characterization with molecular phylogenetic analyses using five DNA loci: internal transcribed spacer (ITS), 28S rDNA, intergenic spacer (IGS), RNA polymerase II subunit 2 (RPB2), and β-tubulin (TUB). This study led to the discovery of three newly described species (E. clematidis sp. nov. on Clematis spp., E. limoniicola sp. nov. on Limonium spp., and E. paeoniae-suffruticosae sp. nov. on Paeonia × suffruticosa and two newly recorded species from China (E. malvae on Malva pusilla and E. punicae on Punica granatum). Notably, our phylogenetic framework demonstrates that incorporating IGS, RPB2, and TUB markers substantially enhances species-level resolution and provides critical insights into cryptic speciation within powdery mildews.